The association between gestational weight gain and perinatal outcomes among underweight women with twin pregnancy in Japan. Issue 2 (23rd February 2022) - Maeda, Yuto; Ogawa, Kohei; Morisaki, Naho; Sago, Haruhiko
Abstract: Objective: To clarify the association between gestational weight gain (GWG) and pregnancy outcomes in underweight women with twin pregnancies in Japan. Methods: This retrospective study derived data from the Japan Society of Obstetrics and Gynecology perinatal database between 2007 and 2015. We included 5049 underweight (pre‐pregnancy body mass index [BMI] <18.5 kg/m 2 ) and 20 812 (BMI ≥18.5 and <25 kg/m 2 ) normal‐weight, twin‐pregnant women. Weekly GWG was stratified into 10 categories. Logistic regression was used to assess the effects of GWG on pregnancy. The primary outcomes evaluated were small‐for‐gestational age (SGA), preterm birth, preeclampsia, and cesarean delivery. Results: In underweight group, high GWG was associated with significant risk reductions in both twins being SGA, at least one twin being SGA, very preterm birth, and extreme preterm birth, while a risk increase was observed in preeclampsia. Compared to women with GWG of 0.25–0.30 kg/week, the risk of preeclampsia was significantly higher in women with GWG >0.35 kg/week. No association was observed between GWG and cesarean delivery. These associations were similar in the normal‐weight group. Conclusion: Underweight women with twin pregnancies showed an inverse association between GWG and SGA or preterm birth. The risk of preeclampsia was higher in women who gained >0.35 kg/week. Synopsis: In underweight women with twin pregnancy, small‐for‐gestational‐age and preterm birth showed negative association with gestational weight gain while preeclampsia showed a positive correlation.